Letter To the Editor: [Relationship between epicardial fat thickness and hypertension] - Şevket Balta; Cengiz Öztürk (KARE Publishing, 2016)
We read the article ' Epicardial fat thickness as associated with left ventricular myocardial performance in patients with newly diagnosed hypertension' by Börekçi et al.(1) The authors aimed to investigate the relationship between epicardial fat thickness(EFT) and tissue Doppler myocardial performance index (TD-MPI), which incorporates both systolic and diastolic left ventricular (LV) function, in newly diagnosed hypertension (HT) patients.They concluded that TD-MPI was independently associated with EFT in patients with newly diagnosed HT. EFT may be used as a predictor of impaired LV global functions in patients with normal left ventricular ejection fraction (LVEF) and newly diagnosed HT. Thanks to the authors for their good contribution of the present study, which is successfully designed and well-documented.